Demographic and Economic Facets of Tourism Trend of Nepal - Khadka, Bimal Kumar; Bhattarai, Rudra Prasad; Karki, Sulav (Journal of Advanced Academic Research, 2025)
Tourism is a vital driver of Nepal’s economy, contributing to GDP, employment, and rural livelihoods, yet the sector has been shaped by political instability, natural disasters, and global crises such as the COVID-19 pandemic. This study examines demographic and economic trends in Nepal’s tourism sector from 2000 to 2024, with the objective of identifying long-term patterns and their implications for sustainable development, while highlighting the urgent need for responsive and forward-looking policy interventions alongside the data. A positivist research philosophy was applied, using quantitative methods and secondary data sourced from the Ministry of Culture, Tourism and Civil Aviation, Nepal Rastra Bank, Nepal Tourism Board, and World Bank. Descriptive statistics and regression analysis were employed to analyze tourist arrivals, demographic shifts, and GDP contributions. Results indicate a steady increase in international tourist arrivals from 463,684 in 2000 to a record 1.19 million in 2019, before plunging to 230,085 in 2020 due to COVID-19, with recovery reaching 1.01 million by 2023. Male tourists consistently dominated (55–60%), though the gender gap narrowed after 2010, while the majority of arrivals belonged to the 16–45 age group, underscoring Nepal’s appeal to younger and middle-aged travelers. India accounted for over 20% of arrivals, followed by the USA, UK, and China, with Chinese tourists peaking at 169,543 in 2019 before collapsing during the pandemic. Economically, tourism’s contribution to GDP declined from around 3.4% in 2000 to an average of 2% in the 2010s, with regression analysis (y = –0.0587x + 120.05; R² = 0.3478) confirming this downward trend. Overall, Nepal’s tourism demonstrates resilience yet requires diversification, sustainable strategies, and urgent policy alignment to ensure long-term growth.